2012
DOI: 10.1038/emboj.2012.231
|View full text |Cite
|
Sign up to set email alerts
|

E2F7 and E2F8 promote angiogenesis through transcriptional activation of VEGFA in cooperation with HIF1

Abstract: The E2F family of transcription factors plays an important role in controlling cell-cycle progression. While this is their best-known function, we report here novel functions for the newest members of the E2F family, E2F7 and E2F8 (E2F7/8). We show that simultaneous deletion of E2F7/8 in zebrafish and mice leads to severe vascular defects during embryonic development. Using a panel of transgenic zebrafish with fluorescent-labelled blood vessels, we demonstrate that E2F7/8 are essential for proper formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
137
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(160 citation statements)
references
References 50 publications
(89 reference statements)
23
137
0
Order By: Relevance
“…We also analyzed the expression level of two different HIFalpha subunits (HIF1A and EPAS1) and shown that only HIF1A is up-regulated in adipose tissue upon obesity and that development of insulin resistance/ glucose intolerance does not affect it. These results agree with data Weijts et al [28] that HIF1 in cooperation with another transcription factors (E2F8 and E2F7) promote angiogenesis through transcriptional activation of VEGFA.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We also analyzed the expression level of two different HIFalpha subunits (HIF1A and EPAS1) and shown that only HIF1A is up-regulated in adipose tissue upon obesity and that development of insulin resistance/ glucose intolerance does not affect it. These results agree with data Weijts et al [28] that HIF1 in cooperation with another transcription factors (E2F8 and E2F7) promote angiogenesis through transcriptional activation of VEGFA.…”
Section: Discussionsupporting
confidence: 83%
“…There is also data that transcription factor E2F8 creates complexes with other members of E2F family of transcription factors and coordinates various cellular functions through the regulation of the expression of target genes, thereby regulating cell cycle, apoptosis, and angiogenesis, including transcriptional activation of VEGFA in cooperation with HIF1 [26][27][28]. There is data [29] that metabolic reprogramming of cancer cells without tumor suppressor LKB1 is realized through HIF1 [29].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Several studies have associated atypical E2Fs in cell proliferation, differentiation and apoptosis, embryo development, angiogenesis, polyploidization of hepatocytes and trophoblast giant cells (TGC) and tumorigenesis. 7,9,[16][17][18][19][20][21][22][23] However, the expression, regulation and function of atypical E2Fs in mouse uterus during early pregnancy are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, we showed that elevated E2F7 levels in SCC are associated with increased binding of E2F7 to the RacGAP1 promoter and increased expression of RacGAP1 in SCCs. E2F7 is traditionally considered to be a transcriptional repressor; however, it has also been shown that E2F7 can function as a direct transcriptional activator of the VEGFA promoter via the formation of an E2F7-HIF1a transcriptional complex (41). Similarly, E2F7 has been shown to bind the Sphk1 promoter in SCC cells and is associated with increased Sphk1 transcription (15).…”
Section: Discussionmentioning
confidence: 99%